Non-Invasive Imaging of Neuroanatomical Structures and Neural Activation with High-Resolution MRI - Herberholz, Jens; Mishra, Subrata; Uma, Divya; Germann, Markus W.; Edwards, Donald H.; Potter, Kimberlee (Frontiers in Behavioral Neuroscience, 2011)
Several years ago, manganese-enhanced magnetic resonance imaging (MEMRI) was introduced as a new powerful tool to image active brain areas and to identify neural connections in living, non-human animals. Primarily restricted to studies in rodents and later adapted for bird species, MEMRI has recently been discovered as a useful technique for neuroimaging of invertebrate animals. Using crayfish as a model system, we highlight the advantages of MEMRI over conventional techniques for imaging of small nervous systems. MEMRI can be applied to image invertebrate nervous systems at relatively high spatial resolution, and permits identification of stimulus-evoked neural activation non-invasively. Since the selection of specific imaging parameters is critical for successful in vivo micro-imaging, we present an overview of different experimental conditions that are best suited for invertebrates. We also compare the effects of hardware and software specifications on image quality, and provide detailed descriptions of the steps necessary to prepare animals for successful imaging sessions. Careful consideration of hardware, software, experiments, and specimen preparation will promote a better understanding of this novel technique and facilitate future MEMRI studies in other laboratories.